The impact of tumor metabolic activity assessed by 18F-FET amino acid PET imaging in particle radiotherapy of high-grade glioma patients - Waltenberger, Maria; Furkel, Jennifer; Röhrich, Manuel; Salome, Patrick; Debus, Charlotte; Tawk, Bouchra; Gahlawat, Aoife Ward; Kudak, Andreas; Dostal, Matthias; Wirkner, Ute; Schwager, Christian; Herold-Mende, Christel; et al. (Frontiers in Oncology, 2022)
Background Selective uptake of (18)F-fluoro-ethyl-tyrosine (18F-FET) is used in high-grade glioma (HGG) to assess tumor metabolic activity via positron emission tomography (PET). We aim to investigate its value for target volume definition, as a prognosticator, and associations with whole blood transcriptome liquid biopsy (WBT lbx) – for which we recently reported feasibility to mirror tumor characteristics and response to particle irradiation in recurrent high-grade glioma (rHGG). Methods 18F-FET-PET data from n=43 patients with primary glioblastoma (pGBM) and n=33 patients with rHGG was assessed. pGBM patients were irradiated with photons and sequential proton/carbon boost, rHGG patients were treated with carbon re-irradiation (CIR). WBT (Illumina HumanHT-12 Expression BeadChips) lbx was available for n=9 patients from the rHGG cohort. PET isocontour (40-70% SUVmax, 10% steps) and MRI-based treatment volumes (MRIvol) were compared using the Conformity Index (CI) (pGBM: n=22, rHGG: n=27). Associations with WBT lbx data were tested on gene expression level, inferred pathways activity scores (PROGENy) and from transcriptome estimated cell fractions (CIBERSORT, xCell). Results In pGBM, median SUVmax was higher in PET acquired pre radiotherapy (4.1, Range (R) 1.5-7.8; n=20) vs. during radiotherapy (3.3, R 1.5-5.7, n=23; p=0.03) and in non-resected (4.7, R 2.9-7.9; n=11) vs. resected tumors (3.3, R 1.5-7.8, n=32; p=0.01). In rHGG, a trend towards higher SUVmax values in grade IV tumors was observed (p=0.13). Median MRIvol was 39.32 (R 8.75-129.93) cm³ in pGBM (n=22) and 20.77 (R 0.63-128.44) cm³ in rHGG patients (n=27). The highest median CI was observed for 50% isodose (pGBM: 0.45; rHGG: 0.43, all tumors), with 70% (40%) isodose in grade III (IV) rHGG tumors (median CI: 0.38 and 0.49). High SUVmax was linked to shorter survival in pGBM (>3.3: p=0.001, OR 6.0 [2.1-17.4]) and rHGG (>2.8: p=0.02, OR 4.1 [1.2-13.9]). SUVmax showed associations with inferred monocyte fractions, hypoxia, TGFbeta pathway activity and links to immune checkpoint gene expression from WBT lbx. Conclusion Benefits of 18F-FET-PET imaging on GTV definition for particle radiotherapy warrants further evaluation. SUVmax might assist in prognostic stratification of HGG patients for particle radiotherapy, highlights heterogeneity in rHGG and is positively associated with unfavorable signatures in peripheral whole blood transcriptomes.